Simulation Study of a Membrane Reactor for Ultrapure Hydrogen Recovery from Methanol Steam Reforming Reaction under Periodic Steady-State - Lemnouer Chibane (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2018)
Steam reforming of methanol over Cu/ZnO/Al2O3 catalyst was theoretically studied under created unsteady state. A mathematical approach was proposed to evaluate the effect of periodic inputs on reactor performance. The efficacy of the periodic separating reactor in term of pure hydrogen and of methanol conversion was measured during the reaction of methanol steam reforming. The obtained results showed that under certain operating conditions the periodic operation can be used advantageously to increase the reactor ability up to a level higher than the maximal steady-state. Moreover, our findings showed that the pumping of hydrogen through the membrane was stimulated by the effect of periodic operations. The predicted results suggested that the created unsteady state mode by using a square wave function could give the better performances compared to the sinusoidal mode.